Revealing the Transformation of Moroccan Islamic Family Law - Adib Syauqi; Rahmat Hidayat; Efrinaldi Efrinaldi (Tafáqquh: Jurnal Penelitian Dan Kajian Keislaman, 2025)
Mudawwanah al-Usra Morocco as a result of the transformation of family law that has relevance in today's times. for that, this research will reveal how the process of transforming family law in Morocco to produce a family law rule that is relevant to the times. This research uses a library research method and data collection techniques by reading literature that can be used as a source according to this research. The results showed that the bookkeeping of the 1957 Moroccan family law adopted the classical fiqh book so changes were made again afterwards. the Moroccan law book, namely Mudawwana al-usra, is the final form of many changes that have been made before. This one is the result of radical changes by the committee in charge. Historically, the old mudawwana book still fully refers to the fiqh books which are old culture. Thus, some rights were not fulfilled. This change has completed the shortcomings of the previous books.